Responsabilidade civil das instituições de ensino nas ocorrências de bullying - Telles, Leticia Dalbosco (2021)
This dissertation studies the different aspects of civil liability of students for acts of physical and psychological violence practiced by students, as well as in incidents of bullying within school, to this end, the work analyzes the nuances of civil liability of children and adolescents, the responsibility of parents for minor children, the civil liability of private schools. When analyzing and classifying bullying and its implications for the development of children and adolescents, the study shows the relevance of the theme and the seriousness of the consequences in adult life, both victims and aggressors. The right to education as a right social and duty of the State, to be considered as the only means to enable social transformation and intellectual enrichment, given the guarantee provided in article 6 of the Federal Constitution. Effective educational policies and capable of generating moral, political and social awareness, equally guaranteed in the constitutional text. The interdisciplinary approach of the work sought to integrate law, psychology, pedagogy and sociology. Regarding the research into the civil liability of parents for the acts of their children under age, the study focuses on civil law, the status of children and adolescents, as well as within the limits established therein. About the civil liability of private schools, it was found that, as it is delimited in the list of established consumption, governed by the Consumer Protection Code, is objective. Furthermore, the research sought to analyze the possibility of education coming to demand return actions against minors and their guardians, it was found that doctrine and jurisprudence diverge on the subject, with possible, but essential that the school effectively proves the absence of blame.